Aplicação da análise hierárquica como ferramenta de tomada de decisão para escolha do compósito de reforço com polímeros reforçados com fibras - Perelles, D. H.; Medeiros, M. F.; Garcez, M. R. (Revista ALCONPAT, 2013)
Strengthening structures with Fiber Reinforced Polymers (FRP) is an alternative that has been used in interventions performed on reinforced concrete elements. Carbon fibers are the most used in the formation of composite reinforcement used in civil works. There is, however, possible to expand the options of forming fibers using the composite fibers of aramid and glass. As an alternative decision-making tool, the Analytic Hierarchy Process, based on criteria analyzed qualitatively and quantitatively, will be used in this work for the evaluation of carbon, aramid and glass fibers in order to obtain what material would be more suitable for theimplementation of a structural reinforcement considering how key parameters of analysis material costs and the tensions and strains that may exhibit elements. This decision-making tool showed useful and can be considered suitable to select different FRP systems.Keywords: Structural strengthening, fiber-reinforced polymers, carbon, aramid, glass, hierarchical analysis method